2003
DOI: 10.1021/jp0348777
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport and Back Reaction in Solid-State Dye-Sensitized Solar Cells:  A Study Using Intensity-Modulated Photovoltage and Photocurrent Spectroscopy

Abstract: Solid-state dye-sensitized solar cells employing spiro-MeOTAD [2,2′7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene] as a hole transport phase were studied by intensity modulated photocurrent spectroscopy (IMPS) and intensity modulated photovoltage spectroscopy (IMVS) over a wide range of illumination intensity. The IMPS and IMVS responses provide information about charge transport and electronhole recombination, respectively. For the range of light intensities investigated, the dynamic photocur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
339
4
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 366 publications
(365 citation statements)
references
References 18 publications
21
339
4
1
Order By: Relevance
“…68,72,[125][126][127] It was found that both the effective electron diffusion coefficient, D n , and the effective electron lifetime, t n , 128,129 that are measured become a function of the steady state. 13,68,72,[129][130][131][132][133][134][135] Using quasi-equilibrium arguments, the variations of both diffusion coefficient and lifetime were attributed to the statistics of electrons in the material, which deviates from dilution, as described by thermodynamic factors. 136 The varying D n was recognized as a chemical diffusion coefficient, 55,127 and the correlation between variations of D n and t n , 135 was explained by a common origin of their variations in an exponential distribution in the bandgap.…”
Section: Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…68,72,[125][126][127] It was found that both the effective electron diffusion coefficient, D n , and the effective electron lifetime, t n , 128,129 that are measured become a function of the steady state. 13,68,72,[129][130][131][132][133][134][135] Using quasi-equilibrium arguments, the variations of both diffusion coefficient and lifetime were attributed to the statistics of electrons in the material, which deviates from dilution, as described by thermodynamic factors. 136 The varying D n was recognized as a chemical diffusion coefficient, 55,127 and the correlation between variations of D n and t n , 135 was explained by a common origin of their variations in an exponential distribution in the bandgap.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…13,68,72,[129][130][131][132][133][134][135] Using quasi-equilibrium arguments, the variations of both diffusion coefficient and lifetime were attributed to the statistics of electrons in the material, which deviates from dilution, as described by thermodynamic factors. 136 The varying D n was recognized as a chemical diffusion coefficient, 55,127 and the correlation between variations of D n and t n , 135 was explained by a common origin of their variations in an exponential distribution in the bandgap. 95,136 The application of the multiple trapping model in DSC will be described in detail in section 3.4.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…from a fraction of a per cent 2 to over 4%. 20 The main draw back of these cells has been fast interfacial electron-hole recombination reducing the diffusion length of the conduction band electrons to a few microns 21 as compared to 20-100 microns for the electrolyte based DSC. As a consequence, the film thickness employed in these cells is only 2 microns which is insufficient to harvest the sunlight by the adsorbed sensitizer, thus reducing the resultant photocurrent.…”
Section: Solid State Dscmentioning
confidence: 99%
“…In nanoparticle films, the nature of electron transport in oxide nanoparticle films is well understood using timeresolved photocurrent and photovoltage measurements and the corresponding modeling study. [113,114,115] It is found that the electron transport in nanoparticle films is through a trapping-detrapping diffusion process, in which the photogenerated electrons interact with charge traps as they undertake a random walk through the nanoparticle network. In FF is the fill factor, which describes the power extraction efficiency of solar cells, and P in (mW/cm 2 ) is the overall illumination power incident on the solar cells.…”
Section: Chapter 5 Zno Based Dye Sensitized Solar Cellsmentioning
confidence: 99%